Photochemical Synthesis of cis, trans, cis‐1, 2, 3, 4‐Tetrakis(diphenylphosphanyl)buta‐1, 3‐diene and Its Metal Coordination. Issue 46 (8th November 2018) - Prock, Johannes; Ehrmann, Katharina; Viertl, Wolfgang; Pehn, Richard; Pann, Johann; Roithmeyer, Helena; Bendig, Marvin; Rodríguez Villalón, Alba; Kopacka, Holger; Dumfort, Alexander; Oberhauser, Werner; Clausing, Simon T.; et al.
Abstract : The new bis(bidentate) tetraphosphane cis, trans, cis ‐1, 2, 3, 4‐tetrakis(diphenylphosphanyl)buta‐1, 3‐diene (dppbd) (7 ) was obtained by applying a photochemical synthetic protocol. The key step of the photochemical reaction consisted of an intramolecular [2+2] cycloaddition involving a C–C double and triple bond of the Pt‐dimer species of the formula [Pt2 Cl4 (dppa)( trans ‐dppen)] (2 ) {dppa = 1, 2‐bis(diphenylphosphanyl)acetylene and dppen = 1, 2‐bis(diphenylphosphanyl)ethene} leading to [Pt2 Cl4 (dppbd)] (5 ). The asymmetrically bridged precursor complex2 was obtained by combinatorial chemistry. Single crystal X‐ray structure analyses of2 and5 proved that the intramolecular photochemical reaction occurred. Cyanolysis of5 gave7, which was oxidized to dppbdO4 (8 ). Compounds7, 8, and the Pd II dimer complex [Pd2 Cl4 (dppbd)] (9 ) were characterized in the solid state by a single‐crystal X‐ray structure analysis. Interesting photophysial properties emerged from the UV/Vis spectra acquired for7 and the dimer Os complexes meso ‐Δ, Λ/Λ, Δ‐[Os2 (bpy)4 (dppbd)](PF6 )4 (10 ) and rac ‐Δ, Δ/Λ, Λ‐[Os2 (bpy)4 (dppbd)](PF6 )4 (11 ). Abstract : An intramolecular photochemical reaction between 1, 2‐ trans ‐bis(diphenylphosphanyl)ethene and 1, 2‐bis(diphenylphosphanyl)acetylene within a dimetallic Pt II complex gave selectively cis, trans, cis ‐1, 2, 3, 4‐tetra‐kis(diphenylphosphanyl)buta‐1, 3‐diene. Its bis‐chelating nature makes it suitable to access bimetallic chromophores applicable for photochemical hydrogen production.